Digital Video Source Identification Based on Container’s Structure Analysis - Raquel Ramos Lopez; Elena Almaraz Luengo; Ana Lucila Sandoval Orozco; Luis Javier Garcia Villalba (IEEE Access, 2020)
The mobile device ecosystem has dramatically evolved over the last few years, since users have openly embraced a massive use of mobile phones for different purposes: professional use, personal use, etc. Digital videos can be used to define legal responsibilities or as part of the evidence in trials. The forensic analysis of digital videos becomes very relevant to determine the origin and authenticity of a video in order to link an individual with a device, place or event. The field of forensic analysis of digital videos is constantly facing new and direct challenges. Even though the basic principles of this discipline remain unchanged, numerous issues appear every year that require new procedures and tools. Therefore, it is necessary to provide forensic analysts with techniques to identify the origin of multimedia content. In this paper, the topic of source identification in open scenarios will be discussed, since analysts do not know in advance the set of cameras to which a video belongs so they find it difficult to identify its source. This approach is similar to real-life situations since in most cases, analysts are unaware of the set of video cameras. This paper aims to create a technique that identifies the source of digital videos generated by digital devices through the use of unsupervised algorithms based on the analysis of the structure of multimedia video devices.